2023
DOI: 10.1093/eurjpc/zwad158
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic hypertension and major adverse events: a systematic review and meta-analysis

Abstract: Introduction The role of orthostatic hypertension (OHT) in cardiovascular disease (CVD) and mortality is unclear. We aimed to determine if this association exists through a systematic review and meta-analysis. Methods Study inclusion criteria included: (i) any observational/interventional studies of participants aged ≥18 years (ii) which assessed the relationship between OHT and (iii) at least one outcome measure – all-cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Finally, a recent meta-analysis confirmed that orthostatic hypertension is associated with increased mortality. 22 Frailty is theoretically defined as a clinically recognizable state of increased vulnerability resulting from an aging-associated decline in reserve function across multiple physiological systems. The Fried criteria are the most commonly used measurement of performance (walking speed, grip strength) and are scored based on relative values in a population.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a recent meta-analysis confirmed that orthostatic hypertension is associated with increased mortality. 22 Frailty is theoretically defined as a clinically recognizable state of increased vulnerability resulting from an aging-associated decline in reserve function across multiple physiological systems. The Fried criteria are the most commonly used measurement of performance (walking speed, grip strength) and are scored based on relative values in a population.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, orthostatic hypertension (OHTN) role in cardiovascular disease is notable in elderly. Pasdar et al showed systolic OHT was associated with increased risk of mortality, cognitive impairment, cardiovascular and brain comorbidities [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest that there is no generally accepted definition of orthostatic hypertension, but a resent consensus document that was published in this Journal made the distinction between an exaggerated pressor response, defined as a sustained systolic blood pressure increase of at least 20 mmHg when changing from the supine to the standing position, and orthostatic hypertension, when an exaggerated pressor response is associated with upright systolic blood pressure of at least 140 mmHg [4,5]. Population studies find similar prevalence of both extremes of blood pressure response to standing, orthostatic hypotension, and orthostatic hypertension, and epidemiological studies indicate that both conditions herald increased cardiovascular risk [6][7][8]. Even less pronounced changes in blood pressure with standing not reaching these diagnostic cutoff levels may be associated with poor outcomes.…”
mentioning
confidence: 99%